Analysis on visitor behaviour and satisfaction about green tourism in rural and mountain villages [Korean] - Kim, Jong-Ho; Jeon, Jun-Heon; Lee, Dukjae; Kim, Seong-Il; Kim, Tong-Il (2007)
This study aims to provide fundamental information for introducing activity-oriented tourism to the Mountain Village Development Project through survey on visitors to mountain villages, and to compare with the characteristics of visitors among three different types of villages such as “Mountain Ecological Village”, “Rural Theme Village”, and “Rural Experience Village”. With a structured questionnaire, direct survey was implemented to visitors to rural and mountain tourism villages. It was revealed that visitors to “Mountain ecological village” usually stayed with family over night and satisfied with surrounding natural environment, which was compared to visitors to other types of rural villages. This suggested that activity-oriented tourism should be introduced to the Mountain Village Development Project in order to promote the participation of visitors with family, which vitalised the mountain villages by using their surrounding natural environment.